The Vagaries of Fashion Pina Bausch's Orfeo ed Eurydice arrives at the Paris Opera - Meisner, Nadine (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Pina Bausch's pared-down movement is as lapidary as the antique world from which the narrative derives. Designer Rolf Borzik's genius was to understand the importance of emptiness. PALABRAS CLAVE: Pina Bausch, Orfeo ed Eurydice, Nelken.